Atividade de inteligência : uma proposta de controle judicial - Martins Júnior, Ayrton Figueiredo (2015)
The intelligence activity is a function developed primarily by state agencies, which refers to the production of sensitive knowledge, intended for use in public policies and authorities decisions. Currently, intelligence has gained notoriety through major invasion of privacy scandals, for instance the case of us espionage against other countries and authorities, as verified incident related to Brazil. However, such activities also gain space in private settings, in the business world. In this context, intelligence is confused to espionage and investigation, noting that, in today's world, more and more we have experienced a society in which the systemic surveillance stages for conflict with fundamental rights such as privacy and the exercise of vigilance. With the analysis of the social influence of intelligence, in this work, we sought to establish legal boundaries for their performance. There was an assimilation of the Brazilian constitutional environment and the need for accountability over the informational activities, as a form of respect for fundamental rights. Based on decisions of foreign courts and application of such understandings by the brazilian judiciary, we proposed a judicial control over the activity of strategic intelligence, which needs more regulation on the use of information sources. At the end we analyze legislative and constitutional proposals of legal bounderies for the intelligence activity.